(untitled) (Bangladesh Journal of Zoology, 2016)
A total of 29 species of frugivorous birds were recorded from the Madhupur National Park during July 2007 to December 2008. Among the frugivorous birds, 16 (55.2%) were absolutely seed gulpers, 2 (6.9%) seed gulpers as well as seed discarders and 5 (17.2%) were fully seed predators. The frugivorous birds were observed more active during early morning (23 species, 79.3%) and late afternoon (20 species, 69%), of which 16 (55.2%) were common in both time frames. Frugivorous birds mainly preferred fruit followed by nectars, seeds and buds. Ficus benghalensis was the top most preferred food plant to the birds. Berries were highly preferred (29.7%) by the birds. The preferred fruit diameter ranged from 16.5 to 19.6 mm (18.1 ± 0.8). Black colour and mild sweet fruit was highly preferred by the birds. Bangladesh J. Zool. 43(2): 173-187, 2015